2016
DOI: 10.3126/jtd.v2i0.15439
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Issues in Nepal: A Study on Graduates' Perception

Abstract: The study was carried to explore the perception of graduates of mechanical engineering of Technical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Young people's experiences of intervention quality included three themes, curriculum and content, instruction and instructor, and management and administration. The majority of participants in 13 studies that contained evidence of curriculum and content reported negative experiences (Apunda et al 2017;Bhurtel 2016;Botea et al 2015 Young people's learning experiences were also affected by the quality of instruction and instructors (Adhikari 2018;Apunda et al 2017;Bhurtel 2016;Ling 2015;Sedighi et al 2015;Veazey 2014). While few participants considered their instructors competent (Apunda et al 2017), others lamented the textbook-based authoritarian pedagogy that discouraged them to develop intellectual curiosity and critical thinking ability (Veazey 2014).…”
Section: Intervention Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Young people's experiences of intervention quality included three themes, curriculum and content, instruction and instructor, and management and administration. The majority of participants in 13 studies that contained evidence of curriculum and content reported negative experiences (Apunda et al 2017;Bhurtel 2016;Botea et al 2015 Young people's learning experiences were also affected by the quality of instruction and instructors (Adhikari 2018;Apunda et al 2017;Bhurtel 2016;Ling 2015;Sedighi et al 2015;Veazey 2014). While few participants considered their instructors competent (Apunda et al 2017), others lamented the textbook-based authoritarian pedagogy that discouraged them to develop intellectual curiosity and critical thinking ability (Veazey 2014).…”
Section: Intervention Qualitymentioning
confidence: 99%
“…In addition, ineffective administration and management of interventions compromised participants' learning (Adhikari 2018;Botea et al 2015;Bhurtel 2016;Korzh 2013;Ling 2015;Nagamuthu et al 2019; Van der Bijl and Lawrence 2019). Poor administrative support for course enrollment, equipment maintenance, stipend distribution and transcript issuance disrupted young people's study and even made some participants quit.…”
Section: Intervention Qualitymentioning
confidence: 99%
See 3 more Smart Citations